Wearable Fluidic Fabric with Excellent Heat Transfer Performance for Sports Recovery - Jing Yang; Ying Xiong; Jinli Piao; Manyui Leung; Guosai Liu; Mingyue Zhu; Shengyang Tang; Lisha Zhang; Xiaoming Tao (Advanced Science)
Abstract Rapid temperature contrast hydrotherapy by water immersion has been utilized by athletes for effective sports recovery. However, its application at some training or competition venues is limited by high water consumption, bucky size, personal hygiene, and inconvenience. Here, a novel portable system equipped with highly effective, lightweight, and hygienic wearable fluidic fabric device is reported, that replaces direct water immersion. The measured heat transfer coefficient between the skin and the fabric is 98.5 W m−2 K−1, which is 92% of that in direct water immersion at 10 °C and significantly higher than that by previously reported cooling garments. The core layer, a flexible heat transfer panel (FHTP), can switch between cold and hot modes (5–40 °C) over an area of 0.3 m2. The contact condition between skin and the deformable FHTP has been considered in a new verified heat transfer model. Optimization of the parameters has resulted in excellent heat transfer performance. This fluidic fabric also holds potential in diverse applications, such as enhancing thermal safety and comfort in extreme environments (e.g., personal thermal management systems and fire‐protection suits), supporting cryotherapy and thermotherapy in rehabilitation and healthcare, and simulation of total tactile sensations in virtual reality.